Nicaragua : First and Second Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2003)
The Financial Sector Assessment Program (FSAP) program has been brought back on track, after some difficulties, in early 2003 (which led to a delay in completing the first review). Although a start has been made in strengthening the banking sector, significant further work is needed. The central bank's asset recovery plan is being implemented, despite strong opposition from vested interests. The authorities reaffirmed their commitment to their growth and poverty-reducing strategy presented in the December 2002 Poverty Reduction Strategy Paper (PRSP) progress report.